Análisis técnico para el accionamiento de una aplicación que permita el control y ventas en el almacén de ropa deportiva "Cristhian Sport" ubicado en la ciudad de Babahoyo - Montoya Vera, Irvin Fernando (2021)
In recent years there has been a notable increase in the importance of information systems in the development of business activity. The control and sales systems integrate the different functions that improve customer service processes; from the use of specific business logic, which facilitate calculations and decisions around the improvement of the commercialization process. The sportswear store "Cristhian Sport" located in the city of Babahoyo, has a dynamism, a competitive spirit, but the current imposition of a globalized market and the rush to implement new technologies to achieve business sustainability, increasingly weighs on the development of the warehouse. All routine tasks of collecting, transmitting, recording and reviewing information in the warehouse are carried out manually. Through the feasibility study carried out in the warehouse, it was evidenced that the system is viable to carry out. The owner stated that he does have the economic resources necessary for its development and implementation and showed his optimism knowing the advantage they will have by having a control and sales system.